2012
DOI: 10.1016/j.cub.2012.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Enhancement of Visual Attention and Neural Oscillations in the Human Brain

Abstract: SummaryCognitive processes such as visual perception and selective attention induce specific patterns of brain oscillations [1–6]. The neurochemical bases of these spectral changes in neural activity are largely unknown, but neuromodulators are thought to regulate processing [7–9]. The cholinergic system is linked to attentional function in vivo [10–13], whereas separate in vitro studies show that cholinergic agonists induce high-frequency oscillations in slice preparations [14–16]. This has led to theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
119
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 43 publications
15
119
5
Order By: Relevance
“…Psychopharmacological neuroimaging studies in humans have indeed reported activation decreases in areas such as the parietal cortex in response to nicotine (e.g., Thiel et al, 2005;Vossel et al, 2008), but this effect is predominantly seen during invalidly cued trials and interpreted as facilitated attentional shifting or enhanced processing efficiency. In contrast, studies using cholinesterase inhibitors have reported an enhancement of voluntary attentional modulation at the behavioral and neural level (Rokem et al, 2010;Bauer et al, 2012). Similarly, muscarinic blockade with scopolamine reduces spatial attentional top-down modulation of responses to visual stimuli in visual cortex (Herrero et al, 2008), and theoretical modeling has shown that inhibitory drive by muscarinic receptors may effectively render the system more sensitive to feedback influences (i.e., attentional modulation) (Deco and Thiele, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Psychopharmacological neuroimaging studies in humans have indeed reported activation decreases in areas such as the parietal cortex in response to nicotine (e.g., Thiel et al, 2005;Vossel et al, 2008), but this effect is predominantly seen during invalidly cued trials and interpreted as facilitated attentional shifting or enhanced processing efficiency. In contrast, studies using cholinesterase inhibitors have reported an enhancement of voluntary attentional modulation at the behavioral and neural level (Rokem et al, 2010;Bauer et al, 2012). Similarly, muscarinic blockade with scopolamine reduces spatial attentional top-down modulation of responses to visual stimuli in visual cortex (Herrero et al, 2008), and theoretical modeling has shown that inhibitory drive by muscarinic receptors may effectively render the system more sensitive to feedback influences (i.e., attentional modulation) (Deco and Thiele, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Precisely timed cholinergic transients could be essential for synchronizing cortical neuronal output driven by salient cues, thereby coordinating local network activity recruited by a cue (33,34). Moreover, the selection of cues for guiding the behavior per se may be mediated by fronto-visual oscillations that are generated by trial-based, phasic cholinergic signaling (35). Such neuronal coordination through coherence therefore could be necessary for the engagement of a particular motor plan for executing selected cue-guided responses.…”
Section: Discussionmentioning
confidence: 99%
“…The task-related boosting (or suppression) of neural oscillations at specific frequencies between cortical regions can enhance performance in processes involved in task selection, attention and memory (Marshall et al, 2004;Lakatos et al, 2008;Bauer et al, 2012;Helfrich et al, 2014). Both rTMS and tDCS can modify ongoing oscillatory activity, and in so doing, may mimic or augment the amplitude of normal endogenous neural oscillations to promote task performance and cortical connectivity.…”
Section: Modulating Local Cortical Synchronizationmentioning
confidence: 99%